Efektifitas Peyuluhan Kesehatan Gigi Dan Mulut Dengan Media Video Melalui WhatsApp Dalam Meningkatkan Derajat Kesehatan Gigi Dan Mulut Di Panti Asuhan Yos Sudarso Jakarta - Jusuf Kristianto; Dwi Priharti; Abral Abral (Politeknik Kesehatan Kemenkes RI Jakarta I, 2018)
One way to improve your child's behavior in keeping oral health is to provide dental health education on how to brush your teeth is good and right with using tools or proper and appropriate media AIDS Promotif as part of the effort or the branch of health science has two sides i.e. side of science and art. Side of the art, i.e., the practitioner or the application of health promotion is supporting, for other health programs to improve the community in maintaining and improving health is no exception of oral health. Most of the inhabitants of brushing your teeth every day while bathing in the morning or afternoon shower. Custom correct brushing Indonesia residents only 2.3% (Riskesdas, 2013). The research method uses Quasi experiment with control group design. The study was conducted on two intervention groups. The number of samples is 30 for the intervention and control groups. Statistical test using dependent t-test, independent t-test.In this study, there was a significant decrease in OHIS from 2.1 down to 1.162In the group with a tooth brushing program and accompanied by counseling accompanied by video through WhatsApp. The results showed that there is a difference towards improved oral hygiene among groups given by group WhatsApp interventions and not shipped WhatsApp, where p = 0.001 < 0.05, The research results with extension demonstration of brushing teeth proved to be an increase in the degree of oral hygiene (OHIS) in foster care at the Yos Sudarso Cilandak, South JakartaThe results showed that there were differences between groups and groups given with groups that were not given WhatsApp, where p = 0.001 <0.05, The results of the study showed that counseling with a demonstration with a tooth brushing video was proven to increase the degree of oral hygiene (OHIS) in foster children in Yos Sudarso, Cilandak, South Jakarta. It is advisable to dental health personnel to use modification to tooth brushing demonstrations and reinforced with videos through Whattapps in order to improve the degree of oral hygiene which will ultimately reduce the incidence of cavities Keywords: WhatsApp Interactive Video , Caregiver Roles, Degree of Dental and Oral Hygiene (OHIS)